2021
DOI: 10.2147/ppa.s329891
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Health Applications Among Patients Diagnosed with Chronic Diseases in Jazan, Saudi Arabia During the COVID-19 Pandemic

Abstract: Purpose: Health applications are employed to aid patients with chronic diseases in effective long-term disease management. This investigation aims to measure the utilization of health applications among patients diagnosed with chronic conditions during the COVID-19 pandemic. Methods: This cross-sectional investigation was conducted in the Jazan region in Saudi Arabia between October 2020 and March 2021. Data were collected during interviews using a semi-structured questionnaire. The questionnaire collected ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…This may support previous findings, showing that general primary care physicians do not examine the patients properly and fail to adhere to diabetes management guidelines (18), though the availability of random glucose tests at primary care units may assist in a more rapid diagnosis of diabetes. Our results are consistent with (28) where a third of the population used health care applications for diabetes management. However, a recent study found that 47% of the Saudi population used the SEHA application to schedule appointments at chronic disease clinics (29).…”
Section: Discussionsupporting
confidence: 90%
“…This may support previous findings, showing that general primary care physicians do not examine the patients properly and fail to adhere to diabetes management guidelines (18), though the availability of random glucose tests at primary care units may assist in a more rapid diagnosis of diabetes. Our results are consistent with (28) where a third of the population used health care applications for diabetes management. However, a recent study found that 47% of the Saudi population used the SEHA application to schedule appointments at chronic disease clinics (29).…”
Section: Discussionsupporting
confidence: 90%
“…The massive burden on the health care system has changed people's perspective, and they find it convenient to consult alternative medical practitioners [29] and electronic channels for information and management [30][31][32][33][34]. Although the percentage of participants seeking care from alternative health practitioners such as chiropractors and podiatrist was low (10% and 13%), the association with misconceptions emphasizes the need to evaluate the knowledge and training of alternative health care practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the application had been recently developed (during the COVID-19 outbreak) and focuses on common problems such as diabetes and hypertension. Another reason may be the limited usage of these applications by the elderly population [33].…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in SA found that people with chronic diseases have low use of health apps because they do not know that health-related apps exist, they cannot use the apps due to lack of knowledge, and they consider the apps unnecessary. Consequently, efforts should be made to encourage people with chronic diseases to use health apps [ 15 ].…”
Section: Discussionmentioning
confidence: 99%